Where to donate: The geographical distribution of corporate philanthropy in China - Li Ji; Cunjie Tao; Bofu Deng (China Journal of Accounting Research, 2021)
An emerging body of literature has demonstrated that corporate philanthropy can be an important part of a company's business strategy. However, we know relatively little about how companies allocate philanthropic resources to achieve their strategic targets. Using geographical distribution data on corporate philanthropy in China from 2009 to 2016, we provide robust evidence of companies' revenue-driven regional favoritism. Specifically, companies donate more to regions where they obtain revenue than to other regions. Further evidence suggests that this revenue-driven regional favoritism may have both reputational and political motivations. Further analysis suggests that China's targeted poverty alleviation policy has compromised revenue-driven regional favoritism while increasing the amount of money donated to poor regions. Overall, we enrich understanding of decision-making on corporate philanthropy. We also demonstrate that companies can use the geographical distribution of corporate philanthropy strategically to obtain consumer and government favor in regions where they operate. The results also provide evidence at the micro company level of the effect of China's implementation of a targeted poverty alleviation policy.
Keywords: 650; Corporate philanthropy; Geographical distribution; Reputational motivation; Political motivation; Targeted poverty alleviation